2014
DOI: 10.1111/ene.12545
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome is associated with cardio/cerebrovascular events and mortality in end‐stage renal disease

Abstract: ESRD patients with RLS demonstrated an increased likelihood of cardio/cerebrovascular events and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
1
37
1
Order By: Relevance
“…A recent cross-sectional study between control group, renal transplantation group and hemodialysis group found that prevalence in renal transplantation is significantly lower than in hemodialysis patients (Kahvecioglu et al, 2016). RLS is very prevalent in end-stage renal disease patients, and hemodialysis patients with RLS were found to have a higher risk of muscle atrophy (Giannaki et al, 2011), cardio/cerebrovascular events and mortality (Lin C.H. et al, 2015).…”
Section: Secondary Rlsmentioning
confidence: 99%
“…A recent cross-sectional study between control group, renal transplantation group and hemodialysis group found that prevalence in renal transplantation is significantly lower than in hemodialysis patients (Kahvecioglu et al, 2016). RLS is very prevalent in end-stage renal disease patients, and hemodialysis patients with RLS were found to have a higher risk of muscle atrophy (Giannaki et al, 2011), cardio/cerebrovascular events and mortality (Lin C.H. et al, 2015).…”
Section: Secondary Rlsmentioning
confidence: 99%
“…RLS/WED had been associated with an increased risk of developing cardiovascular disease both in primary [19,20,21,22] and uremic forms [6,11,23,24]. Some studies also found that RLS/WED is associated with enhanced mortality in ESRD patients [6,8,11,22,25], particularly those with severe forms of RLS/WED [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased morbidity and mortality has been demonstrated in patients with RLS associated with end-stage renal disease, an established secondary cause of RLS(Lin et al, 2015; Winkelman, Chertow, & Lazarus, 1996). These data underline the importance of both primary and secondary RLS as causes of acute distress and predictors of adverse health and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%